DISCLOSURE DAN PSIKOLOGI INVESTOR - Windu Mulyasari (FEB Universitas Sultan Ageng Tirtayasa, 2016)
AbstractQuestions about rational investor and efficiency of the securities market continues to increase, because the evidence indicates that when shares are mispriced on the market value efficiently. Those problems are very important to accountants, because of the possibility of the provision of information cannot meet the needs of investors in decision-making. Furthermore, when the securities market is not fully efficient, the increase in financial reporting will help reduce inefficiency, and is expected to improve the operation of the securities market. Securities market inefficiencies are explained because investor behavior can be studied in behavioral finance. The study provides a basis on why investors behave inefficiently, and does not reflect the information available. The study behavioral finance has not been done in the capital markets. Research in behavioral studies can be carried out with experimental studies. This needs to be taken into consideration to make a study seeking direct evidence of investor behavior. The purpose of this study is to describe how the information content of financial statements that are described by the theory of efficient markets experienced an anomaly, and that there is also asymmetry of information on financial statements so that the information contained in the information gap between investors. Asymmetry of information is expected to decrease with the full disclosure of the company however, was the response of different investors. Therefore, the phenomenon is explained by behavioral finance tested. Keywords: Disclosure, Behavioural Finance, Market Eficiency Abstrak Pertanyaan tentang investor rasional dan efisiensi pasar sekuritas terus meningkat, karena bukti menunjukkan bahwa ketika saham dinilai secara salah pada nilai pasar secara efisien. Masalah-masalah tersebut sangat penting bagi akuntan, karena kemungkinan penyediaan informasi tidak dapat memenuhi kebutuhan investor dalam pengambilan keputusan. Selanjutnya, ketika pasar sekuritas tidak sepenuhnya efisien, peningkatan pelaporan keuangan akan membantu mengurangi inefisiensi, dan diharapkan dapat meningkatkan operasi pasar sekuritas. Inefisiensi pasar sekuritas dijelaskan karena perilaku investor dapat dipelajari dalam keuangan perilaku. Studi ini memberikan dasar mengapa investor berperilaku tidak efisien, dan tidak mencerminkan informasi yang tersedia. Studi perilaku keuangan belum dilakukan di pasar modal. Penelitian dalam studi perilaku dapat dilakukan dengan studi eksperimental. Ini perlu dipertimbangkan untuk membuat penelitian mencari bukti langsung dari perilaku investor. Tujuan dari penelitian ini adalah untuk mendeskripsikan bagaimana kandungan informasi laporan keuangan yang digambarkan oleh teori pasar efisien mengalami anomali, dan bahwa ada juga asimetri informasi pada laporan keuangan sehingga informasi yang terdapat dalam kesenjangan informasi antara investor . Asimetri informasi diharapkan menurun dengan pengungkapan penuh perusahaan, bagaimanapun, adalah respon dari investor yang berbeda. Oleh karena itu, fenomena tersebut dijelaskan oleh keuangan perilaku yang diuji. Kata kunci: Pengungkapan, Perilaku Keuangan, Efisiensi Pasar